Decrease in Morbidity and Mortality by Cervical Cancer - Ruy Roberto Porto Ascenso Rosa (Universidade de Santa Cruz do Sul, 2016)
Background and Objectives: cervical cancer deaths can be avoided through of the early detection and timely handling, which are in the screening recommendations, for women and their health care professionals. The objective of this article is to itemize about the historical background of actions taken to fight this cancer and the method currently used as prevention of uterine cervical neoplasms. Contents: according to studied the literature, the control and prevention were specific and did not includ all the country, so it was not possible to obtain strong impact in reducing mortality. Conclusion: the current prevention strategies is an effective method able of reducing the occurrence of further cases, however we see the need the women's adhesion and that the health professionals improve the catchment and user embracement.